S-[4-(Trimethylammonio)phenyl] thiosulfate, an aromatic organic thiosulfate - Chen, J.X.; Lang, J.P.; Ng, S.W.; Zain, Sharifuddin Md; Zhang, Y.; Xu, Q.F. (2004)
The title compound, C9H13NO3S2, exists as a zwitterion with crystallographic mirror symmetry. The central S atom of the S2O3 group adopts a slightly distorted tetrahedral coordination geometry. The S-S bond length is 2.1137 (7) Å, while the S-O bond lengths are in the range 1.4417 (12)-1.457 (2) Å. The zwitterions in the crystal adopt a head-to-tail arrangement, which leads to the formation of a three-dimensional network through C-H ⋯ O hydrogen bonds.